2003
DOI: 10.1177/152660280301000602
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of In-Stent Restenosis after Carotid Angioplasty: A Case-Control Study

Abstract: The present study, far from being exhaustive on the subject, indicates that patients who develop restenosis after carotid endarterectomy are also prone to develop restenosis after CAS; moreover, although strongly recommended for postsurgical restenosis, CAS carries a greater risk of in-stent restenosis in this subgroup, thus reducing the benefits of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 42 publications
1
9
1
Order By: Relevance
“…Other studies evaluating the impact of premorbid risk factors on complications have found significant risk from diabetes 34. However, our results and an earlier study by Setacci et al 21 found no correlation with vascular risk factors.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Other studies evaluating the impact of premorbid risk factors on complications have found significant risk from diabetes 34. However, our results and an earlier study by Setacci et al 21 found no correlation with vascular risk factors.…”
Section: Discussioncontrasting
confidence: 84%
“…Several other studies have also reported higher rates of ISR in patients with hostile-neck lesions 20–23. This has been disputed by a report by Eskandari et al , in which the rate of ISR in patients with hostile-neck lesions was not significantly higher than in patients with atherosclerotic lesions (4.5% vs 2.0%, respectively) 21 24…”
Section: Discussionmentioning
confidence: 91%
“…Specific risk factors in the development of restenosis after CAS remains to be elucidated: some studies have identified advanced age [27, 28], hyperglycemia [27, 29], smoke [27] and previous CEA [30]. In our study group, out of all the evaluated clinical radiological and procedural variables, multivariate analysis reveal that the residual stenosis after CAS is a stronger predictor of restenosis with a consistent increased risk of restenosis (1.091 per % unit of residual stenosis).…”
Section: Discussionmentioning
confidence: 99%
“…Suggested predictors of restenosis after CAS are advanced age [23], female gender [23], prior revascularization treatment [24,25], asymptomatic lesion [26], suboptimal technical result with residual stenosis [24], use of balloon-expandable stents [26], implantation of multiple stents [23], and elevated postprocedural serum levels of acute-phase reactants [24]. The definite role of these factors has not yet been confirmed in large studies.…”
Section: Discussionmentioning
confidence: 99%